Measuring technology addiction among part-time students in UiTM Kota Bharu - Aminuddin, Azwan Shah; Md Zamri, Muhammad Aiman; Abdul Rahman, Muhammad Arif; Dzulkifli, Nor Idayu; Rose Man, Nur Shashirah (Journal of Islamic, Social, Economics and Development, 2026)
The digital revolution has fundamentally altered the global educational landscape, with technology now permeating every facet of student life. While essential for modern business literacy, this "always-on" culture fosters a precarious dual nature, particularly among part-time students at the Faculty of Business and Management (FBM) in UiTM Kota Bharu. This study investigates the factors influencing technology addiction, examining the roles of emotional intelligence, psychological well-being, and technology usage. A quantitative, non-experimental correlational research design was adopted, utilizing a structured questionnaire distributed to 124 respondents selected via simple random sampling. Results indicate moderate levels for all variables: Emotional Intelligence (M = 3.58), Psychological Well-Being (M = 3.53), Technology Usage (M = 2.96), and Technology Addiction (M = 3.01). Pearson Correlation analysis revealed significant and positive relationships between the independent variables and the dependent variable. Notably, Emotional Intelligence demonstrated a very strong correlation with technology addiction (r = .974), while Psychological Well-Being (r = .672) and Technology Usage (r = .759) showed strong positive correlations. This research highlights the critical need for academic interventions to bolster internal resilience and emotional regulation among future business leaders to mitigate digital dependency.